Modelling the influence of biotic plant stress on atmospheric aerosol particle processes throughout a growing season - D. Taipale (Copernicus Publications, 2021)
Most trees emit volatile organic compounds (VOCs) continuously throughout their life, but the rate of emission and spectrum of emitted VOCs become substantially altered when the trees experience stress. Despite this, models to predict the emissions of VOCs do not account for perturbations caused by biotic plant stress. Considering that such stresses have generally been forecast to increase in both frequency and severity in the future climate, the neglect of stress-induced plant emissions in models might be one of the key obstacles for realistic climate change predictions, since changes in VOC concentrations are known to greatly influence atmospheric aerosol processes. Thus, we constructed a model to study the impact of biotic plant stresses on new particle formation and growth throughout a full growing season. We simulated the influence on aerosol processes caused by herbivory by the European gypsy moth (Lymantria dispar) and autumnal moth (Epirrita autumnata) feeding on pedunculate oak (Quercus robur) and mountain birch (Betula pubescens var. pumila), respectively, and also fungal infections of pedunculate oak and balsam poplar (Populus balsamifera var. suaveolens) by oak powdery mildew (Erysiphe alphitoides) and poplar rust (Melampsora larici-populina), respectively. Our modelling results indicate that all the investigated plant stresses are capable of substantially perturbing both the number and size of aerosol particles in atmospherically relevant conditions, with increases in the amount of newly formed particles by up to about an order of magnitude and additional daily growth of up to almost 50 nm. We also showed that it can be more important to account for biotic plant stresses in models for local and regional predictions of new particle formation and growth during the time of infestation or infection than significant variations in, e.g. leaf area index and temperature and light conditions, which are currently the main parameters controlling predictions of VOC emissions. Our study thus demonstrates that biotic plant stress can be highly atmospherically relevant. To validate our findings, field measurements are urgently needed to quantify the role of stress emissions in atmospheric aerosol processes and for making integration of biotic plant stress emission responses into numerical models for prediction of atmospheric chemistry and physics, including climate change projection models, possible.